IDEOLOGICAL STRENGTHENING, STRATEGIC LEADERSHIP, AND DEPERSONALIZATION: THE TRANSFORMATION OF THE INDONESIAN DEMOCRATIC PARTY OF STRUGGLE 1999-2019 - Kristiyanto, Hasto; Hanief, A (CosmoGov: Jurnal Ilmu Pemerintahan, 2022)
Since 1999, the votes of the Indonesian Democratic Party of Struggle (PDIP) have always been relatively superior, despite having to deal with various internal and external problems. By winning the elections, PDIP has given and placed the best party cadres in public positions in the legislature and executive, which directly influences the course of the Indonesian nation. Various survey results show that PDIP is still the top choice with the highest electability. Based on these data, the purpose of this study is to analyze the institutional transformation of PDI, especially in strengthening ideology and the process of party depersonalization. The method used is a literature study and the data analysis technique is carried out by analyzing the three dimensions of the concept of party institutionalization from Harmel et al. (2019), namely internal institutionalization, external institutionalization, and objective institutionalization (objective durability). From the method used, it was found that the party had carried out organizational transformation during the 1999-2019 period. PDIP also continues to consolidate to advance democracy, because political parties are the key to maintaining and developing the quality of democracy. It was also found that political institutionalization is important. An important aspect of party institutionalization is the strength of ideology as a party-political concept that underlies the ideals, struggles, and norms of the party. Finally, the partys ability to depersonalize shows significant results in party institutionalization.gb777